Chronic Sleep Deprivation as a Risk Factor for Cognitive Decline and Mood Disorders: Neurobiological Mechanisms and Therapeutic Implications - Paweł Stępowski; Hanna Rzepka; Mateusz Tajster (Journal of Education, Health and Sport, 2026)
Chronic sleep deprivation has emerged as a significant and modifiable risk factor for cognitive decline and mood disorders, with neurobiological consequences that extend far beyond transient impairment of alertness. Modern societies are characterised by widespread, voluntary curtailment of sleep, with surveys consistently indicating that large proportions of adults in industrialised nations sleep fewer than the recommended seven to nine hours per night (Watson et al., 2015). The consequences of this pervasive sleep deficit include measurable impairments in sustained attention, working memory, executive function, and decision-making, as well as substantially elevated risks of developing major depressive disorder, anxiety disorders, and bipolar spectrum conditions (Lim and Dinges, 2010; Baglioni et al., 2011). At the neurobiological level, sleep deprivation disrupts adenosine homeostasis, impairs prefrontal cortical function, dysregulates hypothalamic-pituitary-adrenal axis activity, elevates systemic inflammation, and suppresses hippocampal neurogenesis—mechanisms that collectively explain the breadth and severity of observed clinical effects (Xie et al., 2013; Irwin, 2015). This review synthesises current evidence on sleep physiology, the neurobiological basis of sleep deprivation effects, specific cognitive and mood consequences, vulnerable populations, diagnostic approaches, therapeutic strategies, and public health implications, with the goal of providing a comprehensive foundation for clinical recognition and intervention.